Pediatric Multiple Sclerosis in the United Arab Emirates: Characteristics From a Multicenter Study and Global Comparison. (May 2018) - Ismail, Fatima Y.; Gordon-Lipkin, Eliza; Huether, Katherine; Blair, Iain; Szólics, Miklós; Alsaadi, Taoufik; Aziz, Faisal; Suleiman, Jehan; Schiess, Nicoline
We delineate the clinical characteristics, incidence, and prevalence of pediatric-onset multiple sclerosis in Abu Dhabi, United Arab Emirates, from 2010 to 2014. Eighty-two patients (65% female) were identified. Fifty-three (64.6%) were Emiratis (45 from Abu Dhabi and 8 from 5 other emirates) and 29 were expatriates. Mean age of onset was 15.9 years overall, 15.3 years in males and 16.3 years in females. Patients with onset before age 12 years presented with visual symptoms while those with onset after age 12 years presented with a mixture of visual, motor and sensory symptoms. Interferon beta-1a was the most frequently used disease-modifying therapy (48%). In Abu Dhabi Emirati nationals, the age- and sex-adjusted prevalences were 26/100 000 for males and 36/100 000 for females. The total incidence in Emirati nationals from 2010 to 2014 was 2.3/100 000 for ages 10 to 14 years and 7.2/100 000 for ages 15 to 19 years. By comparison with international cohorts, the incidence of pediatric-onset multiple sclerosis in Abu Dhabi is higher whereas gender distribution is similar.